Proceedings of the 11th International Workshop "Data analysis methods for software systems" - Bernatavičienė, Jolita (Vilnius University Proceedings, 2019)
DAMSS-2019 is the 11th international workshop on data analysis methods for software systems, organized in Druskininkai, Lithuania, atthe end of the year. The same place and the same time every year. History of the workshop starts from 2009 with 16 presentations. The ideaof such workshop came up at the Institute of Mathematics and Informatics that now is the Institute of Data Science and Digital Technologiesof Vilnius University. The Lithuanian Academy of Sciences and the Lithuanian Computer Society supported this idea. This idea got approvalboth in the Lithuanian research community and abroad. The number of this year presentations is 77. The number of registered participantsis 127 from 9 countries. The main goal of the workshop is to introduce the research undertaken at Lithuanian and foreign universities in thefields of data science and software engineering. Annual organization of the workshop allows the fast interchanging of new ideas among theresearch community. Even 9 companies and institutions supported the workshop this year. This means that the topics of the workshop areactual for business, too. Topics of the workshop cover Artificial Intelligence, Big data, Bioinformatics, Blockchain technologies, BusinessRules Software Engineering, Data Science, Deep Learning, Digital Technologies, High-Performance Computing, Machine Learning, MedicalInformatics, Modelling Educational Data, Ontological Engineering, Optimization in Data Science, Signal Processing, Visualization Methods forMultidimensional Data. A special session and discussions are organized about topical business problems that may be solved together with theresearch community. This book gives an overview of all presentations of DAMSS-2019.